Análise do processo de tomada de decisão em investimentos de tecnologia da informação: estudo de caso múltiplo - Lopes, Ricardo Danilo Campos (Universidade do Vale do Rio dos Sinos, 2010)
The market has presented an evolution after the industrial era, from a generation focused on production to a stage that focuses on information. With this change in behavior organizations need to fit the new demands of the market and then IT gets a crucial role in several businesses. With the insertion of IT in the market, the level of competitiveness among companies has a characteristic towards information, pointing a strategic value each time more intense due to the capacity of management of this information. Searching the need to remain competitive, organizations register values increasingly significant in IT investment, opening a lacuna to the questions regarding the return of these investments because the return of these evaluations are not presented in a direct and quantitative way, being necessary the junction of several variables for evaluating investments in IT. Facing this unknown, the decision-making becomes more assertive because managers lack the tools and methods to evaluate this investments. The importance of more assertive decisions, also follow IT investments, therefore mostly represent large percentage of the organizations billing. The decision varies in many spheres and situations with this assertive in certain portfolios in a company; it does not guarantee success of that portfolio in other companies. Therewith the research has focused on the execution of a case study addressing the decision-making in companies that have investments in IT, focusing on two organizations that are market leaders. Thus, evaluating the various situations in the process of IT and analyzing variables in decision making.
Keywords: Tecnologia da informação; Tomada de decisão; Investimentos em TI; Estudo de caso; Information technology; Decision making; Investments in IT; Case study; ACCNPQ::Ciências Sociais Aplicadas::Administração